Brain morphological changes and associated functional connectivity and lag structures in women with primary dysmenorrhea during the pain-free periovulatory phase - Su, Xing; Liu, Huiping; Wang, Hong; Yao, Nan; Wu, Yutong; An, Simeng; Li, Youjun; Zhang, Ming; Huang, Zi-Gang; Dun, Wanghuan (The journal of pain, 2025)
Primary dysmenorrhea(PDM) is defined as painful menstrual cramps without any evident pathology, exhibiting central nervous system(CNS) sensitivity and functional and structural changes in brain regions responsible for pain perception and modulation. Previous imaging studies primarily focused on functional changes, with only a limited number of studies investigated changes in brain morphology, and these studies generally used small sample sizes. It remains largely unknown whether brain structural changes are coupled with functional changes in patients with PDM, as well as the association between structural alterations and prostaglandin levels. This study used voxel-based morphometry(VBM) analysis to examine total and regional gray matter volume(GMV) increases and decreases in a larger sample of 59 patients with PDM and 56 healthy controls(HC) during the pain-free periovulatory phase. Abnormally increased regional GMV were involved in emotional regulation, pain rumination, and network integration functions while decreased regional GMV were involved in pain perception, emotional response, attention regulation, and pain-related visual cortex. This study found that the left mid-cingulate cortex is an important node in pain anticipation and attention, modulation of the salience network(SN), regulation of spinal nociceptive processing via descending control pathways for patients with PDM. Finally, this study examined the directional signaling patterns among these altered regional GMV using Time-Delay method and found that structural alterations were accompanied by changes in functional integration. Our findings provide preliminary insights into the CNS mechanisms underlying the link between structural and functional changes and subjective pain perception, offering valuable information for clinical pain interventions in patients with PDM. PERSPECTIVE: This study used voxel-based morphometry, Time-Delay and NBS-predict to examine gray matter volume alterations and related directional signaling patterns in patients with PDM. Structural alterations accompanied by changes in functional segregation were found during pain-free periovulatory phase.